Public Perception of Indonesian Television Broadcasting Programs Quality - FX Ari Agung Prastowo; Dadang Rahmat Hidayat (Fakultas Dakwah UIN Saizu Purwokerto, 2022)
The public's interest in television programs is raised due to their function to increase education and protect the country from conflict or disharmony. According to the function of media, the media has three purposes: as a watchdog, a public forum, and media for public participation. The media also has the assignment to critique the government if they need to be released good regulations for the public. So the researchers are interested in exploring media content, especially television. This research analyzes the public perception of television programs such as news, talk shows, variety shows, infotainment, soap opera, religion, kids' programs, and tourism and culture. In collaboration with Komisi Penyiaran Indonesia (KPI), researchers collect program samples from television from August until December. To collect the data, we held a focus group discussion with eight informants from Universitas Padjadjaran who are experts in media, politics, religion, cinema, and content. The research results show that four programs have an index below the line. The programs include infotainment 2,81; variety shows 2,72; soap operas 2,83, and tourism and culture 2,43. Therefore, producers need to do more in-depth research before creating a show. It is useful for increasing the overall understanding of the target audience's tastes, preferences, characteristics, and knowledge level.